Study on the change of trysin inhibitors (TI) in the seeds of Momordica cochinchinensis during their formation and development - Uyen, Nguyen Quynh; Quang, Le Trong; Thai, Trinh Hong; Ha, Phan Thi; Tran Chau, Pham Thi; Dung, Le Nguyen (Academia Journal of Biology, 2015)
Study on the change of trysin inhibitors (TI) in the seeds of Momordica cochinchinensis during their formation and development